A note on the calculation of firm-specific and skill-specific labor costs from firm-Ievel data - Ulrich Kaiser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2000)
Virtually all empirical firm-level studies on the demand for labor do not include labor cost in the econometric specification. This is due to the fact that business and innovation survey data usually lack information on labor cost. This paper shows how reliable skill-specific and firm-specific labor cost can be calculated from firm-level data on the basis of information on total labor cost and firms' skill mix only. The simple method proposed here is applied to German innovation survey data.
Keywords: J3; C14; 330; labor cost; Kernel density estimation; Arbeitskosten; Unternehmen; Qualifikation; Humankapital; Dekompositionsverfahren; Schätzung; Theorie; Deutschland